Pengaruh Kualitas Pelayanan Pengurusan Nomor Izin Berusaha terhadap Kepuasan Masyarakat di Kabupaten Gresik: Studi pada Sistem Online Single Submission - Elsa Aurelia Margareta; Anggraeny Puspaningtyas; Eddy Wahyudi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze and explain in greater detail the influence of service quality in managing the Business Identification Number (NIB) through the Online Single Submission (OSS) system on public satisfaction at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Gresik Regency. A quantitative research method was employed, using a structured survey design and distributing questionnaires to 105 respondents who had directly utilized and experienced the OSS service. Service quality was measured using the SERVQUAL dimensions tangible, reliability, responsiveness, assurance, and empathy while public satisfaction was assessed based on indicators derived from the Regulation of the Minister of Administrative and Bureaucratic Reform No. 14 of 2017. The collected data were analyzed using simple linear regression to identify the extent of the relationship between variables. The results indicate that service quality has a positive and significant effect on public satisfaction. This means that better, more consistent service quality will increase user satisfaction. The findings confirm that strengthening service quality is essential for improving overall public service performance, especially in digital-based licensing systems.